Perancangan Sistem Smart Home Berbasis Internet of Things Menggunakan Mikrokontroler ESP32 - Elpan Randa Kasih (Institute of Information Technology and Social Science (IITSS), 2021)
A home is the primary place for humans to live, functioning as a space to rest and carry out various activities. With technological advancements, the concept of a conventional home has begun to transform into a smart home utilizing Internet of Things (IoT) technology. This research aims to design and implement a smart home system based on the ESP32 microcontroller that is capable of remotely controlling and monitoring household electronic devices through an application on an Android-based smartphone. The system was implemented in a miniature house equipped with six controllable devices, including lights, air conditioners, water pumps, and room temperature sensors. Data communication between the devices and the user was conducted over an internet network using the Blynk platform. The test results showed that all devices could be controlled and monitored effectively through the application, and system performance was significantly influenced by the stability of the internet connection. Overall, this system is considered an effective initial solution for implementing an IoT-based smart home concept in residential environments.